Microaerobic growth‐decoupled production of α‐ketoglutarate and succinate from xylose in a one‐pot process using Corynebacterium glutamicum. Issue 9 (18th June 2021) - Tenhaef, Niklas; Kappelmann, Jannick; Eich, Arabel; Weiske, Marc; Brieß, Lisette; Brüsseler, Christian; Marienhagen, Jan; Wiechert, Wolfgang; Noack, Stephan
Abstract: Background: Lignocellulosic biomass is the most abundant raw material on earth. Its efficient use for novel bio‐based materials is essential for an emerging bioeconomy. Possible building blocks for such materials are the key TCA‐cycle intermediates α‐ketoglutarate and succinate. These organic acids have a wide range of potential applications, particularly in use as monomers for established or novel biopolymers. Recently, Corynebacterium glutamicum was successfully engineered and evolved towards an improved utilization of d ‐xylose via the Weimberg pathway, yielding the strain WMB2evo . The Weimberg pathway enables a carbon‐efficient C5‐to‐C5 conversion of d ‐xylose to α‐ketoglutarate and a shortcut route to succinate as co‐product in a one‐pot process. Methods and Results: C. glutamicum WMB2evo was grown under dynamic microaerobic conditions on d ‐xylose, leading to the formation of comparably high amounts of succinate and only small amounts of α‐ketoglutarate. Subsequent carbon isotope labeling experiments verified the targeted production route for both products in C. glutamicum WMB2evo . Fed‐batch process development was initiated and the effect of oxygen supply and feeding strategy for a growth‐decoupled co‐production of α‐ketoglutarate and succinate were studied in detail. The finally established fed‐batch production process resulted in the formation of 78.4 mmol L −1 (11.45 g L −1 ) α‐ketoglutarate and 96.2 mmol L −1 (11.36 g L −1 ) succinate. Conclusion: The developed one‐pot process represents a promising approach for the combined supply of bio‐based α‐ketoglutarate and succinate. Future work will focus on tailor‐made down‐stream processing of both organic acids from the fermentation broth to enable their application as building blocks in chemical syntheses. Alternatively, direct conversion of one or both acids via whole‐cell or cell‐free enzymatic approaches can be envisioned; thus, extending the network of value chains starting from cheap and renewable d ‐xylose. Abstract : The Weimberg pathway enables a carbon‐efficient C5‐to‐C5 conversion of xylose to α‐ketoglutarate and a shortcut route to succinate as established platform chemical. In this study, we employed the recently engineered and evolved strain C. glutamicum WMB2evo to establish a one‐pot cultivation process for co‐production of α‐ketoglutarate and succinate from xylose.